DEFINITION OF BASIC AND ADDITIONAL FACTORS AFFECTING THE RELIABILITY AND ENVIRONMENTAL SAFETY AND DRAINAGE MEREZHVODOPOSTACHANNYA - , В. М. (Municipal economy of cities. Series: «Economy science», 2013)
The main factors affecting the environmental safety and reliability of water supply and sanitation. Using a mathematical model, based on graph theory, defined the significance of each of these factors.